Changes in teaching and learning practice in an undergraduate logistics and transportation course using problem-based learning - Guimarães, Leovani; Lima, Renato (Journal of University Teaching and Learning Practice, 2021)
This research paper presents the outcomes of a change in the teaching and learning practices from a traditional lecture-based method to a Problem Based Learning (PBL) curriculum in the undergraduate Logistics & Transportation (L&T) course at the Federal University of Itajubá (UNIFEI), Brazil. Detailed PBL practices adoption and the perception by the students of the PBL process are explored in survey research using a mixed-methods approach. The data was collected in two subsequent semesters of the L&T course, with different PBL scenarios and students, gathering quantitative and qualitative data. It was demonstrated that aligned with the theory on PBL, the majority of the students, over 91%, appreciated the benefits of the PBL-based practices in all course dimensions, with a strong perception of L&T teaching and learning improvements. Researchers and faculty involved in university teaching and learning can use PBL detailed practices, including problem scenarios and theoretical framework to design their own PBL classes to improve student learning and can also use the questionnaire structure and statistical tests for adoption in future implementations. The study is one of the few to provide a change in teaching and learning practices, associated with a valid and reliable two-stage survey covering the course concepts and learning objectives modelled by Factor Analysis, and, going beyond to provide PBL process impact and adaptations due to COVID-19 pandemic.